A Bluetooth And Vision Controlled Automatic Guided Vehicle - Wong, Chun Xiang; Soon, Chin Fhong (Emerging Advances in Integrated Technology, 2022)
The aim of this project is to construct a Bluetooth (2.4GHz) and vision controlled auto guided vehicle (AGV) for use during the COVID-19 pandemic. The auto guided vehicle can be maneuvered by using an application in mobile phone or auto guided function. The auto guided function of the vehicle is following the label that is affixed on the user. Bluetooth communication was applied to control the AGV at a maximum distance of 10 m. The auto guided vehicle can carry a maximum of 10 kg load. The vision system applied could track and follow the human movement affixed with a label. The best following distance of the AGV developed is within 80cm and the angle of detection is 55°. The auto guided vehicle can reduce the risk of the user in contacting the AGV and hence, minimising the risk of virus infection. It also helps the senior user to save energy in pushing the heavy cart.